ANALYSIS OF NMR SPECTRA OF BISINDOLE ALKALOIDS ARUNDO DONAX L. WITH EXPERIMENTS 1D, 2D. (Scientific journal of the Fergana State University, 2024)
New bisindole alkaloids were isolated from the alkaloids of the root part of A. donax L. - arundinin, arundavin, arundamine, arundanin, arundacin, arundarin, and arundafin. Their structures were elucidated based on data chemical and spectral methods. In the article NMR sprctroscopy of 1H and 13C nuclea, including data from homo- and heteronuclear modes of 1D, 2D experiments and chemical transformation (Hess methylation).